2010
DOI: 10.1111/j.1551-2916.2010.03838.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Photocatalytic Cements: Understanding TiO2 Surface Chemistry to Control and Modulate Photocatalytic Performances

Abstract: The present work addresses the aggregation/dispersion properties of two commercial titanias for application as photocatalysts in concrete technology. A microsized m‐TiO2 (average particle size 153.7 ± 48.1 nm) and a nanosized n‐TiO2 (average particle size 18.4 ± 5.0 nm) have been tested in different ionic media (Na+, K+, Ca2+, Cl−, SO42−, synthetic cement pore solution) at different pHs and in real cement paste specimens. Results highlighted that ion–ion correlations play a fundamental role in TiO2 particles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 42 publications
5
58
0
1
Order By: Relevance
“…Moreover, oxidation of CNTs by acid mixture, photooxidation wet chemical methods, gas phase treatment, or oxygen plasma can improve CNT stability when they are dispersed in many polar solvents such as ethanol, methanol, isopropanol, and water [30]. Base on the previous study, acid mixture purification of MWCNTs showed a negative charge property [31], which makes TiO 2 rejection easier due to negative charge property of TiO 2 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oxidation of CNTs by acid mixture, photooxidation wet chemical methods, gas phase treatment, or oxygen plasma can improve CNT stability when they are dispersed in many polar solvents such as ethanol, methanol, isopropanol, and water [30]. Base on the previous study, acid mixture purification of MWCNTs showed a negative charge property [31], which makes TiO 2 rejection easier due to negative charge property of TiO 2 [32].…”
Section: Introductionmentioning
confidence: 99%
“…16,32 The decrease was mostly attributed to reduced specific surface area and mass diffusion in large aggregates. However, the two-phase variation of the UV irradiation induced TiO 2 aggregates does not correlate with the change of specific surface area.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The significance of each mechanism depends on the pH. The presumed reason is so as to TiO 2 particle surfaces can adsorb water molecules and forming fresh hydroxyl groups (TiOH) (Folli et al, 2010). This clarification is in agreement with FT-IR results.…”
Section: Optimization Of Ph Paraquatmentioning
confidence: 50%